Cellular clones ; Waging peace in Sagada ; Madama Butterfly [videorecording] - Lazaro, Cheche; Santos, Owen (The Probe Team, 1994)
The technological disadvantages of cellular phones cloners or duplicators of cellular phone lines have victimized cell phone users, making them pay exorbitant fees for calls they never made. Deals with Sagadans declaration of their area as a peace zone. A group of artists want to change opera.